Getting Ahead of Time—Performing Temporal Boundaries to Coordinate Routines under Temporal Uncertainty - Geiger, Daniel; Danner-Schröder, Anja; Kremser, Waldemar (Administrative Science Quarterly, 2021)
In this ethnographic study of firefighters we explore how routines are coordinated under high levels of temporal uncertainty—when the timing of critical events cannot be known in advance and temporal misalignment creates substantial risks. Such conditions render time-consuming incremental and situated forms of temporal structuring—the focus of previous research on temporal coordination—unfeasible. Our findings show that firefighters focused their efforts on enacting temporal autonomy or, as they called it, “getting ahead of time.” They gained temporal autonomy—the capacity to temporally uncouple from the unfolding situation to preserve the ability to adapt to autonomously selected events—by relying on rhythms they developed during training in performing individual routines and by opening up to the evolving situation only when transitioning between routines. Our study contributes to literature on temporal structuring by introducing temporal autonomy as a novel strategy for dealing with temporal contingencies. We also contribute to research on routine dynamics by introducing the performance of temporal boundaries as a previously unrecognized form of coordination within and among routines. Finally, we contribute to process research a method that allows analyzing complex temporal patterns and thus provides a novel way of visualizing processes.